Critical thinking skill development: Analysis of a new learning management model for Thai high schools - Changwong, Ken; Sukkamart, Aukkapong; Sisan, Boonchan (My University, 2018)
Under the vision outlined in Thailand 4.0, critical thinking skills have become one of the key pillars of a new, knowledge-based economy. However, the 2015 Thailand Research Fund study that evaluated the logical thinking and analytical skills of 6,235 students in ten provinces of Thailand, found that the average score was 36.5%, with only 2.09% of all students passing. Recognizing the severity of the crisis, nine experts met in August 2017 as a focus group and were tasked by the researchers to help with the development of a new critical thinking learning management model. From this, a five-step learning management model was conceptualized, which the authors called the ‘PUSCU Model’. By means of cluster random sampling, 69 students were selected, from which two sub-groups were formed. One group of 35 experimental studies students, and one group consisting of 34 traditional learning students. The PUSCU model was tested for 16 weeks, from November 2016 through February 2017. The Statistical Package for the Social Sciences (SPSS) 21 software was used to conduct a one-way Multivariate Analysis Of Variance (MANOVA) to determine whether there were any differences between the control and the experimental groups. The results indicated that the experimental group had higher average scores in terms of critical thinking ability and academic achievement, and its members were satisfied with a high level of the model performance, particularly, with the instructor’s use of the developed learning materials.
Keywords: Critical thinking; High-school students; Learning management; Pucsc model; Secondary education; Thailand 4.0